Local stability of partially restrained rectangular tubes subject to shear, compression, and bending. Issue 3 (1st July 2020) - Bedair, Osama
Abstract : This paper investigates local stability of tube sections subject to shear, compression, and bending. A closed form expression is proposed by idealizing the tube components as partially restrained against rotation and in‐plane translation. The derived expression is validated for limiting conditions with existing design expressions that are available in engineering standards. It is shown that the buckling stress may differ by 38% due to the rotational and lateral restraints. The proposed expressions can be utilized by practitioners to compute buckling load for various applied stress ratios with reasonable accuracy.